PENGENALAN TAJWID SEJAK DINI MELALUI METODE BAGHDADI DI DESA KARANGHAUR - Eka Maulidia; Abdul Muis; R. Achmad Mulyana (An-Nizam, 2023)
Reading the Qur'an properly and correctly is one of the most important knowledge that must be possessed by a child from an early age and Muslims as a basis before studying other sciences. read the Qur'an properly in accordance with the science of Tajwid, the law is Fardhu 'Ain. While reading the Qur'an in accordance with the knowledge of Tajweed, the law is Fardhu Kifayah. So, the science of recitation is knowledge of the rules and ways to read the Qur'an as well as possible. Being aware of the importance of tajwid from an early age and even learning tajwid is very important. Along with the development of the times, the Al-Qur'an learning method has developed. The Al-Baghdadi method is a method of learning the Qur'an. This method is done by spelling it out letter by letter, so this method is usually known as the "spelled" or lubi method. This activity aims to improve the process of learning the Koran at TPA Karanghaur village. Through the learning process, especially learning the Koran, it is hoped that students will be able to read the Koran better, be able to know the origin of a letter so that they will better understand every reading of the verses of the Koran that they read every day.